Tech Start-ups Spurn NASDAQ for London. - Susan Arterian Chang (IEEE spectrum)
Instead of going to NASDAQ for its initial public offering (IPO), Protonex Technology Corp., turned to London's Alternative Investment Market (AIM) to raise US 16.2 million dollars in equity capital. With AIM providing awareness and credibility outside the US market, the Massachussets-based developer of fuel cell systems for military and commercial applications saw Protonex's share price rising to more than 12% since the IPO. For small to midsize technology companies that are short on capital but long on global ambitions, AIM is fast becoming the IPO market of choice. One of AIM's attractions is that it requires no minimum capitalization or issue size. It also features nominated advisors, known as Nomads, whose task is to guide and monitor a company in the years following the IPO